Development of a protocol for detection of SARS-CoV-2 in sputum and endotracheal aspirates using Cepheid Xpert Xpress SARS-CoV-2. Issue 12 (12th December 2020) - Malczynski, Michael; Rezaeian, Saba; Rios, Javier; Dirnberger, Laura; Polanco, Wanda; Zembower, Teresa; Qi, Chao
Abstract : Sputum and endotracheal aspirates (ETs) are not among the vendor-approved specimens for the Cepheid Xpert SARS-CoV-2 assay. However, they are the common lower respiratory tract specimens submitted for laboratory diagnosis. Testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in lower respiratory tract samples is required for the discharge of patients from coronavirus disease (COVID) units at some institutions. We developed a protocol used for testing unliquified viscous sputum or tracheal aspirate with the Cepheid Xpert SARS-CoV-2 assay.